Economic evaluation of cognitive behavioral therapy and Internet‐based guided self‐help for binge‐eating disorder. Issue 2 (18th January 2018) - König, Hans‐Helmut; Bleibler, Florian; Friederich, Hans‐Christoph; Herpertz, Stephan; Lam, Tony; Mayr, Andreas; Schmidt, Frauke; Svaldi, Jennifer; Zipfel, Stephan; Brettschneider, Christian; Hilbert, Anja; de Zwaan, Martina; et al.
Abstract: Objective: To determine the cost‐effectiveness of individual face‐to‐face cognitive behavioral therapy (CBT) compared to therapist guided Internet‐based self‐help (GSH‐I) in overweight or obese adults with binge‐eating disorder (BED). Method: Analysis was conducted alongside the multicenter randomized controlled INTERBED trial. CBT ( n = 76) consisted of up to 20 individual therapy sessions over 4 months. GSH‐I ( n = 71) consisted of 11 modules combining behavioral interventions, exercises including a self‐monitoring food diary, psychoeducation, and 2 face‐to‐face coaching sessions over 4 months. Assessments at baseline, after 4 months (post‐treatment), as well as 6 and 18 months after the end of treatment included health care utilization and sick leave days to calculate direct and indirect costs. Binge‐free days (BFD) were calculated as effect measure based on the German version of the Eating Disorder Examination. The incremental cost‐effectiveness ratio (ICER) was determined, and net benefit regressions, adjusted for comorbidities and baseline differences, were used to derive cost‐effectiveness acceptability curves. Results: After controlling for baseline differences, CBT was associated with non‐significantly more costs (+€2, 539) and BFDs (+40.1) compared with GSH‐I during the 22‐month observation period, resulting in an adjusted ICER of €63 per additional BFD. CBTs probability of being cost‐effective increased above 80% only if societal willingness to pay (WTP) was ≥€250 per BFD. Discussion: We did not find clear evidence for one of the treatments being more cost‐effective. CBT tends to be more effective but also more costly. If the societal WTP for an additional BFD is low, then our results suggest that GSH‐I should rather be adopted.